M. bovis BCG Moreau N-Terminal Loss Leads to a Less Stable Dodecin With Lower Flavin Binding Capacity - Schwarz, Marcos Gustavo Araujo; Luzes, Bianca Gallart Cinelli; Correa, Paloma Rezende; Silva-Gonçalves, Antônio José da; Machado, Lucas de Almeida; Guimarães, Ana Carolina Ramos; Mendonça-Lima, Leila (Frontiers in Cellular and Infection Microbiology, 2021)
Tuberculosis still remains a concerning health problem worldwide. Its etiologic agent, Mycobacterium tuberculosis, continues to be the focus of research to unravel new prophylactic and therapeutic strategies against this disease. The only vaccine in use against tuberculosis is based on the in vitro attenuated strain, M. bovis BCG. Dodecin is a dodecameric complex important for flavin homeostasis in Archea and Eubacteria, and the M. tuberculosis protein is described as thermo- and halostable. M. bovis BCG Moreau, the Brazilian vaccine strain, has a single nucleotide polymorphism in the dodecin start codon, leading to a predicted loss of seven amino acids at the protein N-terminal end. In this work we aimed to characterize the effect of this mutation in the BCG Moreau protein features. Our recombinant protein assays show that the predicted BCG homolog is less thermostable than M.tb’s but maintains its dodecamerization ability, although with a lower riboflavin-binding capacity. These data are corroborated by structural analysis after comparative modeling, showing that the predicted BCG dodecin complex has a lower interaction energy among its monomers and also a distinct electrostatic surface near the flavin binding pocket. However, western blotting assays with the native proteins were unable to detect significant differences between the BCG Moreau and M.tb orthologs, indicating that other factors may be modulating protein structure/function in the bacterial context.